(untitled) (Religious dialogue and cooperation, 2022)
This paper analyses O. O. Shakhmatov’s treatise “The Korsunian Legendaboutthe Volodymyr’s Baptism”. O. O. Shakhmatov proves that the legend about thebaptismof Prince Volodymyr in Korsun (Chersonese), preserved in chronicle and consecratedbytradition, does not correspond to reality, since it does not withstand textual criticism.According to the Shakhmatov’s hypothesis , the chronicler had to coordinateandfusethree independent sources into a single outline, removing too obvious contradictions.Thus, a) according to the first source, Prince Volodymyr was baptized in Kyiv, beingconvinced by a Greek missionary who criticized the faith of Western Christians, Muslimsand Jews and substantiated the exclusivity of Eastern rite Christianity; b) accordingtothe second source, Prince Volodymyr was baptized in Kyiv after he sent his delegatestodifferent countries to “test the faith” and the delegates, amazed by the splendor oftheGreek worship, gave preference to Eastern rite Christianity; c) finally, according tothethirdsource, Prince Volodymyr took the city of Korsun (Chersonese) and, threateningtotakeConstantinople, forced emperor to spouse his sister Anna to himin exchange for baptism.However, when Anna arrived in Korsun, Volodymyr refused to be baptized andsuddenlybecame blind. Nevertheless, eventually he was baptized and miraculously restoredhissight. The existing chronicle is a compilation of the three sources. The followingchaptersof O. O. Shakmatov’s work are dedicated to finding the sources of these three legendsandreconstructing their original form. This article thoroughly analyses O. O. Shakhmatov’streatise, reviews the works of the researchers mentioned by O. O. Shakhmatov, andexamines the primary sources used by him in his treatise.